2018
DOI: 10.3389/fnmol.2018.00367
|View full text |Cite
|
Sign up to set email alerts
|

Glial Cells in the Fish Retinal Nerve Fiber Layer Form Tight Junctions, Separating and Surrounding Axons

Abstract: In the retina of teleost fish, cell addition continues throughout life involving proliferation and axonal growth. To study how this is achieved in a fully functioning retina, we investigated the nerve fiber layer (NFL) of the cichlid fish Astatotilapia burtoni for components that might regulate the extracellular environment. We hypothesized that growing axons are surrounded by different cell structures than signal conducting axons. Using immunohistochemistry and freeze fracture electron microscopy we found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 57 publications
(65 reference statements)
0
11
0
Order By: Relevance
“…A comparative stain for glial markers did not reveal a contorted course of the radial glia fibers in the zebrafish brain (SOM Figure S2). Unfortunately, the DCX antibody does not show reactivity in the zebrafish brain, possibly due to the expression of doublecortin‐like protein kinase but not DCX in zebrafish (Shimomura et al, 2007), although DCX has been reported in other fish groups including the telencephalon of sharks (Docampo‐Seara et al, 2020) and the retina of cichlids (Garcia‐Pradas et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparative stain for glial markers did not reveal a contorted course of the radial glia fibers in the zebrafish brain (SOM Figure S2). Unfortunately, the DCX antibody does not show reactivity in the zebrafish brain, possibly due to the expression of doublecortin‐like protein kinase but not DCX in zebrafish (Shimomura et al, 2007), although DCX has been reported in other fish groups including the telencephalon of sharks (Docampo‐Seara et al, 2020) and the retina of cichlids (Garcia‐Pradas et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the doublecortin (C‐18) sc‐8066 antibody is an affinity purified antibody raised against a peptide at the C‐terminus of the human doublecortin protein. It has been shown to label differentiating neurons next to the peripheral growth zone in the retina of A. burtoni (Garcia‐Pradas et al, 2018). The islet1 antibody is known to bind to a subset of neurons in the zebrafish CNS (Johnson et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…37 These glial cells establish tight junctions and prevent fluid ingress into the axons. 38 Breakdown of this barrier, although possible, should manifest itself with symmetric swelling of the RNFL on both sides of the peak point along with a decrease in RNFL reflectivity. However, thickening of the RNFL occurs focally at and nasal to the peak site of compression, and accompanied by an increase in RNFL reflectance.…”
Section: Discussionmentioning
confidence: 99%
“…This idea emerges in relevant articles on this topic during the last decades: “Fish retinas differ fundamentally from those of other vertebrates because they continue to grow throughout the life of the animal, both by adding new neurons and by stretching existing retinal tissue” [ 32 ]; “In fish and amphibia, retinal stem cells located in the periphery of the retina, the ciliary marginal zone (CMZ), produce new neurons in the retina throughout life” [ 33 ]; “The retina of many fish and amphibians grows throughout life, roughly matching the overall growth of the animal. The new retinal cells are continually added at the anterior margin of the retina, in a circumferential zone of cells […]” [ 34 ]; “The retinas of lower vertebrates grow throughout life from retinal stem cells (RSCs) and retinal progenitor cells (RPCs) at the rim of the retina” [ 35 ]; “In the retina of teleost fish, cell addition continues throughout life involving proliferation and axonal growth” [ 36 ], to name a few. However, studies from our group in the sea lamprey, Petromyzon marinus , and the catshark, Scyliorhinus canicula , revealed the loss of proliferative activity in the retina of adult individuals of these ancient vertebrate groups [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%